(untitled) (Journal of Health, Population and Nutrition, 2009)
Equity and gender, despite being universal concerns for all health programmes in Bangladesh, are often missing in many of the health agenda. The health programmes fail to address these important dimensions unless these are specifically included in the planning stage of a programme and are continually monitored for progress. This paper presents the situation of equity in health in Bangladesh, innovations in monitoring equity in the use of health services in general and by the poor in particular, and impact of targeted non-health interventions on health outcomes of the poor. It was argued that an equitable use of health services might also result in enhanced overall coverage of the services. The findings show that government services at the upazila level are used by the poor proportionately more than they are in the community, while at the private facilities, the situation is reverse. Commonly-used monitoring tools, at times, are not very useful for the programme managers to know how well they are doing in reaching the poor. Use of benefit-incidence ratio may provide a quick feedback to the health facility managers about their extent of serving the poor. Similarly, Lot Quality Assurance Sampling can be an easy-to-use tool for monitoring coverage at the community level requiring a very small sample size. Although health problems are biomedical phenomena, their solutions may include actions beyond the biomedical framework. Studies have shown that non-health interventions targeted towards the poor improve the use of health services and reduce mortality among children in poor households. The study on equity and health deals with various interlocking issues, and the examples and views presented in this paper intend to introduce their importance in designÂing and managing health and development programmes. Key words: Equity; Gender; Health; Health services; Monitoring tools; Bangladesh doi:10.3329/jhpn.v26i3.1902 J Health Popul Nutr 2008 Sept:26(3):378-383